Baseline and Innate Immune Response Characterization of a Zfp30 Knockout Mouse Strain - Laudermilk, Lucas T. (Mamm Genome, 2020)
Airway neutrophilia is correlated with disease severity in a number of chronic and acute pulmonary diseases, and dysregulation of neutrophil chemotaxis can lead to host tissue damage. The gene Zfp30 was previously identified as a candidate regulator of neutrophil recruitment to the lungs and secretion of CXCL1, a potent neutrophil chemokine, in a genome-wide mapping study using the Collaborative Cross. ZFP30 is a putative transcriptional repressor with a KRAB domain capable of inducing heterochromatin formation. Using a CRISPR-mediated knockout mouse model, we investigated the role that Zfp30 plays in recruitment of neutrophils to the lung using models of allergic airway disease and acute lung injury. We found that the Zfp30 null allele did not affect CXCL1 secretion or neutrophil recruitment to the lungs in response to various innate immune stimuli. Intriguingly, despite the lack of neutrophil phenotype, we found there was a significant reduction in the proportion of live Zfp30 homozygous female mutant mice produced from heterozygous matings. This deviation from the expected mendelian ratios implicates Zfp30 in fertility or embryonic development. Overall, our results indicate that Zfp30 is an essential gene but does not influence neutrophilic inflammation in this particular knockout model.